AB0800 Neutrophil: Lymphocyte Ratio and Mean Platelet Volume in Patients with Gout. (15th July 2016) - Balkarli, A.; Dogru, A.; Ugan, Y.; Dogan, G.; Tunc, S.E.; Sahin, M.
Abstract : Background: Gout is a clinical syndrome with increased uric acid concentration, which is caused by inflammatory response against mono sodium urate (MSU) crystals. In gout, neutrophils are involved in inflammatory response and neutrophil activation is dependent to local cytokine production. Mean platelet volume (MPV) and neutrophil:lymphocyte ratio (NLR) are considered as inflammatory markers in several diseases and it is reported that they may have prognostic significance. Objectives: According to current literature, there is no study evaluating MPV and NLR in gout. In this retrospective study, we investigated role of MPV and NLR in determination of inflammation in gout disease. Methods: In this retrospective study, 106 patients with gout (91 men and 15 women) meeting inclusion criteria by patients records and 148 age- and sex-matched healthy controls (128 men and 20 women) were included. Laboratory data during attacks (group I) and intercritical period (group II) were collected in the patient group. Results: Mean age was 59.46±12.93 years in the patient group whereas 59.00±11.33 years in the control group. Age at first attack was 52.00±12.77 years and mean time interval between first 2 attacks was 6.00±5.52 months. There was tophus in 9 patients (8.5%) and family history of gout in 17 patients (16.0%). Compared to group 2 (intercritical period) and control, no significant difference in MPV levels was found in the group 1 (during attack). MPV was similar among three groups. C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were found to be significantly higher in the group I compared to group II. There was significant difference in NLR among three groups. When classified according to presence of tophus, it was seen that MPV and NLR were similar in both groups. Conclusions: The finding of increased NLR during attacks and intercritical period shows that patients with gout are subjected to chronic inflammation. Thus, NLR can be simple, inexpensive and useful diagnostic marker in gout. Studies comparing cytokine levels with NLR will be helpful in elucidating this topic. Disclosure of Interest: None declared